Altered expression of the Olr59, Ethe1, and Slc10a2 genes in the liver of F344 rats by neonatal thyroid hormone disruption. Issue 9 (16th March 2017) - Matsubara, Kana; Nakamura, Naoki; Sanoh, Seigo; Ohta, Shigeru; Kitamura, Shigeyuki; Uramaru, Naoto; Miyagawa, Shinichi; Iguchi, Taisen; Fujimoto, Nariaki
Abstract: Many concerns have been expressed regarding the possible adverse effects of thyroid hormone‐disrupting chemicals in the environment. The disruption of thyroid hormones in the neonatal period may lead to permanent effects on thyroid hormone homeostasis as well as related developmental disorders, as thyroid hormones are essential for regulating the growth and differentiation of many tissues. To understand the long‐term alteration in gene expressions by neonatal administration of thyroid hormone‐like chemicals in general, we identified genes whose expression was altered in the liver, an important component of the thyroid hormone axis, by neonatal exposure to triiodothyronine (T3). T3 was administered to male F344 rats on postnatal days 1, 3, and 5 (week 0). At 8 weeks of age, cDNA microarray analysis was used to identify hepatic genes whose expression was altered by neonatal exposure to T3. Among the up‐regulated genes that were identified, the expression of Olr59, Ethe1, and Slc10a2 increased specifically in rats neonatally exposed to T3. Interestingly, altered hepatic expression of these genes indeed increased when a hydroxylated polybrominated diphenyl ether (PBDE), OH‐BDE42, which is capable of binding to the TR, was given neonatally. Our data demonstrated that neonatal exposure to thyroid hormones could affect the long‐term expression of the genes, which could be useful markers for neonatal effects by thyroid hormone‐disrupting chemicals. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : To understand the long‐term alteration in gene expressions by neonatal administration of thyroid hormone‐like chemicals, we identified hepatic genes whose expression was altered by neonatal exposure to T3 in rats. The cDNA microarray analysis showed that mRNA expression of Olr59, Ethe1, and Slc10a2 increased specifically in rats neonatally exposed to T3. Our data suggest that neonatal thyroid hormone disruption could affect long‐term expression of the genes which would be useful markers for the neonatal endocrine disruption.